PERANAN PERBANKAN SYARIAH DALAM PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH MENURUT EKONOMI SYARIAH - Novitri Ramadhani; Diajeng Regita Nandani; Dini Lestari (EKSYA : Jurnal Ekonomi Syariah, 2023)
In the Indonesian economy, micro, small and medium enterprises are the business group that has the largest number of business actors. Not only that, this group has proven to be resilient to various shocks from the economic crisis. So it is really important to strengthen the MSME group which will certainly involve many parties because the MSME sector itself contributes greatly to employment, improves welfare, reduces the unemployment rate and later eradicates poverty. The characteristics of Islamic banking are far different from conventional banking which uses an interest system, because Islamic banking is based on profit sharing which is developed through both musyarakah and mudharabah financing products. With the presence of Islamic banking, it is hoped that it will have a positive impact on the growth of the real sector. One of the businesses that need to be developed is Micro, Small and Medium Enterprises.